2004
DOI: 10.1099/mic.0.27008-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress-responsive proteins are upregulated in Streptococcus mutans during acid tolerance

Abstract: Streptococcus mutans is an important pathogen in the initiation of dental caries as the bacterium remains metabolically active when the environment becomes acidic. The mechanisms underlying this ability to survive and proliferate at low pH remain an area of intense investigation. Differential two-dimensional electrophoretic proteome analysis of S. mutans grown at steady state in continuous culture at pH 7?0 or pH 5?0 enabled the resolution of 199 cellular and extracellular protein spots with altered levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
4
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 88 publications
(113 reference statements)
5
131
4
2
Order By: Relevance
“…However, since an overall 2?7-fold increase in NADP-dependent glyceraldehyde-3-phosphate dehydrogenase at pH 5?0 represented nearly twice the increase in the cumulative levels of each of the other two enzymes in the alternative oxidative branch of glycolysis, this suggested that NADP-dependent glyceraldehyde-3-phosphate dehydrogenase may indeed be of prime importance in determining this direction. This would be in keeping with the high level of anabolic activity required to maintain the structural integrity of molecules such as proteins and DNA in a non-optimal acidic cytoplasm (Crow & Wittenberger, 1979;Quivey et al, 2001;Len et al, 2004). This notion was supported by the detection of a high level of transketolase (Tkt) solely on 2-DGE gels at pH 5?0.…”
Section: Glycolysismentioning
confidence: 54%
See 1 more Smart Citation
“…However, since an overall 2?7-fold increase in NADP-dependent glyceraldehyde-3-phosphate dehydrogenase at pH 5?0 represented nearly twice the increase in the cumulative levels of each of the other two enzymes in the alternative oxidative branch of glycolysis, this suggested that NADP-dependent glyceraldehyde-3-phosphate dehydrogenase may indeed be of prime importance in determining this direction. This would be in keeping with the high level of anabolic activity required to maintain the structural integrity of molecules such as proteins and DNA in a non-optimal acidic cytoplasm (Crow & Wittenberger, 1979;Quivey et al, 2001;Len et al, 2004). This notion was supported by the detection of a high level of transketolase (Tkt) solely on 2-DGE gels at pH 5?0.…”
Section: Glycolysismentioning
confidence: 54%
“…Of these, 123 were identified by MALDI-TOF analysis and 53 found to be associated with regulatory and/or stressresponsive pathways (Len et al, 2004). The remaining 70 protein spots were associated with metabolism; the majority were associated with glycolysis, alternative acid production and branched-chain amino acid synthesis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The acid stress response has been shown to include increased transcript levels of genes involved in utilization of urease (ureA, ureB, ureC, and ureF) and of nuoF, which encodes an NADH dehydrogenase, which can increase internal cell pH by assisting proton export from the bacterial cell (1,2,5,6,28). A decrease in transcripts encoding the F 0 F 1 ATPase was also observed, which was somewhat surprising since this F 0 F 1 ATPase is considered an important proton extrusion mechanism in several Gram-positive bacterial species, such as Streptococcus mutans (17). Although acid stress responses do not include increases in major virulence factors or biofilm formation, there were noteworthy changes in several global regulators that control the expression of virulence genes and drug efflux transporters (5), such as the SaeRS and ArlRS, two-component regulators, the Ser/Thr kinase PknB, and its phosphatase Stp1.…”
Section: Discussionmentioning
confidence: 94%
“…The aciduricity of this organism has been attributed largely to the proton-extruding F 1 F 0 -ATPase that functions well at pH 5.0 and below, allowing the organism to maintain adequate DpH when the external pH falls to 4.0 and lower (Bender et al, 1986;Cotter & Hill, 2003). Other mechanisms of acid resistance in S. mutans include induction of stress proteins (Hamilton & Svensäter, 1998;Len et al, 2004;Svensäter et al, 1997;Wilkins et al, 2002), changes in membrane-associated proteins and fatty acid composition (Fozo et al, 2007;Hasona et al, 2007), DNA repair enzymes (Hahn et al, 1999;Hanna et al, 2001) and increase in alkali production through several metabolic pathways (Burne et al, 1999;Griswold et al, 2006). Moreover, the ComCDE quorum-sensing system has been found to play a role in cell-density-dependent acid tolerance by S. mutans (Li et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%